EXPERIENCES OF WORKPLACE BULLYING IN WOMEN WORKER - Oktaviana, Mistety; Latiman, Ari (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2024)
This qualitative study aims to describe the experiences of Workplace Bullying in women worker. Workplace Bullying is an act of violence in the work environment, which involves verbal abuse, threats, ostracism, insults, isolation, eliminating opportunities, insinuating, giving harsh criticism, and interfering in other people’s personal affairs. Workplace Bullying cause psychologically and physiologically problems. In this study, the subjects were 3 women who were still actively working at PT X. The interview technique used semi-structured using interview guidelines. The result of this study founds several themes and units of analysis, including factors that cause workplace bullying, who are the bullies, forms of workplace bullying, impacts that received by participants, the reasons why participants persist, the support they received, and about their hopes. It is hoped that this research can become a reference for policy makers to take preventive actions that can minimize the occurrence of workplace bullying. Keywords: workplace, bullying, women, worker